2019
DOI: 10.20944/preprints201906.0285.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lenvatinib as an Initial Treatment in Patients with Intermediate-stage Hepatocellular Carcinoma Beyond up-to-seven Criteria and Child-Pugh A Liver Function: A Proof-of-Concept Study

Abstract: Background: Although transcatheter arterial chemoembolisation (TACE) is the standard of care for intermediate-stage hepatocellular carcinoma (HCC), this is a largely heterogeneous disease that includes a subgroup of patients who do not benefit from TACE. The treatment strategy for this subgroup of patients currently remains an unmet need in clinical practice. Here, we performed a proof-of-concept study that lenvatinib may be more favourable treatment option over TACE as an initial treatment in intermediate-sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 33 publications
0
43
1
Order By: Relevance
“…Currently, there is only one published report in which lenvatinib was compared with TACE. The ORR, median progression‐free survival, and OS for lenvatinib were 73%, 16 months, and 37.9 months, respectively; those for TACE were 33.3%, 3.0 months, and 21.3 months, retrospectively 35 . These results for TACE were considerably different from our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Currently, there is only one published report in which lenvatinib was compared with TACE. The ORR, median progression‐free survival, and OS for lenvatinib were 73%, 16 months, and 37.9 months, respectively; those for TACE were 33.3%, 3.0 months, and 21.3 months, retrospectively 35 . These results for TACE were considerably different from our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although TACE is the standard treatment for intermediate-stage HCC [ 9 ], it is ineffective for suppressing tumor growth in multiple HCC nodules ( 7) when administered alone. LEN is the only first-line agent to demonstrate a survival benefit over TACE in TACE-naive patients out of up-to-seven criteria [ 14 ]. In cases where new nodules exhibiting treatment resistance to LEN are detected, a change from LEN to second-line MTAs is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Hiraoka et al reported that ALBI grade is useful for assessing hepatic function and HCC prognosis [ 17 ]. ALBI grade 1 and preserved liver function are associated with OS or response rate in LEN treatment [ 14 ]. Moreover, Lee et al reported that ALBI grade is an important factor associated with survival in patients with intermediate-stage HCC who underwent TACE [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A propensity-weighted analysis by Kudo and colleagues suggested improved survival with use of systemic therapy compared with TACE in patients with HCC beyond up-toseven criteria. 12 Although thought provoking, these data are nonrandomized, prone to residual confounding, and it is unclear if and what would be the optimal tumor burden threshold to consider systemic therapy instead of locoregional therapy. Appropriate patient selection in these cases is critical and must be considered in light of all treatment options.…”
Section: Rationale For Multidisciplinary Care In Hepatocellular Carcimentioning
confidence: 99%